Adaptive cross-correlation detector for signals of optoelectronic reflective sensors - Bilyy, O.I.; Yaremyk, R.Y.; Kostyukevych, S.O.; Kostyukevych, K.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
A soft- and hardware realization of optoelectronic intellectual sensor for biomedical noninvasive studies based on the analysis of light reflected from living tissues has been described. The main feature of the developed model is use of an adaptive crosscorrelation detector controlled by the digital signal processor. Algorithms and operating mode of detector are defined by the type of particular problem to be solved and conditions of measurements. The proposed model was tested to identify dynamic signals in the following areas: pulsometer, evaluation variability of the cardial rhythm, evaluation of blood saturation by oxygen.